Adesão formal ou real ao antirracismo no Serviço Social? caminhos e descaminhos do debate étnico-racial na categoria profissional - Moreira, Tales Willyan Fornazier (2024)
This work aimed to investigate the rooting process of the ethnic-racial debate and anti racism in Brazilian Social Services, from the middle of the last decade. The analysis undertaken here had as a reference the leading role of professional entities at national level in this process (ABEPSS, CFESS and ENESSO), focusing on the main milestones built from 2017 onwards, since after this period, almost a decade ago, this debate no longer left the radar of organizational entities, occupying an important centrality in their political agendas and decisively crossing the profession. This choice is justified by the fact that these entities are the support of the emancipatory direction of the Ethical-Political Project and follow the movement of history itself, being deeply in tune with the burning issues that are on the agenda for the professional category. In this way, we understand that this process has contributed to Social Work advancing the ethnic-racial debate in the context of training and professional work, building anti-racist theoretical-methodological, ethical-political and technical-interventional skills and abilities. The research had as an elementary hypothesis the fact that, despite important advances in relation to this discussion in recent years, this still constitutes a permanent field of disputes and theoretical-political disagreements, and this hinders the effective rooting of the ethnic political debate. racial, showing a movement of formal adherence to anti-racism in the profession. The research results, however, demonstrate the obstacles and challenges present in this field, but confirm that the accumulations built by Brazilian Social Services allow us to overcome mere formal adherence and move towards effective real adherence to anti-racism in the professional category